The experience of intergenerational interactions and their influence on the mental health of older people living in residential care. - Elizabeth Jane Earl; Debbie Marais (PLoS ONE)
The mental health of an increasing ageing population is an important part of healthcare. Research has explored means to enrich the lives of older adults living in residential settings, including approaches like the Eden Alternative. This is a cross-sectional, qualitative study with a quantitative component. It looks at common mental health conditions (CMHCs) in residential-living older adults in South Africa and describes their experiences of intergenerational interactions with playschool children. Participants completed a questionnaire which included the Geriatric Depression Scale and Geriatric Anxiety Scale and a semi-structured interview. Anxiety and depression were common in the sample with limited awareness of non-pharmacological therapy available at the facility. The intergenerational interactions were experienced positively with emerging themes of belonging, sense of purpose, reminiscence and positive affective experiences, but influenced by participants' preconceptions of children. The study concludes that intergenerational interactions may serve as adjunctive therapy in managing CMHCs in residential-living older adults. Recommendations are made for successful implementation of such programs.